Cultural factors and performance in 21st century businesses - Christiansen, Bryan, 1960-; Branch, John David, 1967-; Karmowska, Joanna, 1967- (Advances in business strategy and competitive advantage., 2020)
"This book examines the role of cultural factors on business productivity and performance"--